Ec maritime zones: The delimitation aspect - Franckx, Eric (1992)
Starting from the premise that regional cooperation is best served by settled maritime boundaries, this article looks into the delimitation practice by European Community (EC) states. First the municipal enactments are considered of those member states actually claiming an exclusive economic zone (EEZ). Special emphasis is given to the delimitation provisions. Since not much uniformity can be found in these provisions, the specific boundary agreements that these countries have so far concluded inter se are then analyzed. A geographical distinction is made between the Baltic Sea, the North Sea, the north Atlantic, and the Mediterranean in this respect. The article concludes that not much uniformity can be found in these delimitation agreements either. These boundary questions are therefore believed to continue to burden further EEZ cooperation between EC member states. © 1992 Taylor & Francis Group, LLC. SCOPUS: ar.j info:eu-repo/semantics/published